World Malaria Report: time to acknowledge Plasmodium knowlesi malaria - Bridget E. Barber; Giri S. Rajahram; Matthew J. Grigg; Timothy William; Nicholas M. Anstey (Malaria Journal, 2017)
Abstract Background The 2016 World Health Organization (WHO) World Malaria Report documents substantial progress towards control and elimination of malaria. However, major challenges remain. In some regions of Southeast Asia, the simian parasite Plasmodium knowlesi has emerged as an important cause of human malaria, and the authors believe this species warrants regular inclusion in the World Malaria Report. Main text Plasmodium knowlesi is the most common cause of malaria in Malaysia, and cases have also been reported in nearly all countries of Southeast Asia. Outside of Malaysia, P. knowlesi is frequently misdiagnosed by microscopy as Plasmodium falciparum or Plasmodium vivax. Thus, P. knowlesi may be underdiagnosed in affected regions and its true incidence underestimated. Acknowledgement in the World Malaria Report of the regional importance of P. knowlesi will facilitate efforts to improve surveillance of this emerging parasite. Furthermore, increased recognition will likely lead to improved delivery of effective treatment for this potentially fatal infection, as has occurred in Malaysia where P. knowlesi case-fatality rates have fallen despite rising incidence. In a number of knowlesi-endemic countries, substantial progress has been made towards the elimination of P. vivax and P. falciparum. However, efforts to eliminate these human-only species should not preclude efforts to reduce human malaria from P. knowlesi. The regional importance of knowlesi malaria was recognized by the WHO with its recent Evidence Review Group meeting on knowlesi malaria to address strategies for prevention and mitigation. Conclusion The WHO World Malaria Report has an appropriate focus on falciparum and vivax malaria, the major causes of global mortality and morbidity. However, the authors hope that in future years this important publication will also incorporate data on the progress and challenges in reducing knowlesi malaria in regions where transmission occurs.